Performance and Microstructural Analysis of Lightweight Concrete Blended with Nanosilica under Sulfate Attack - Paola Vargas; Natalia A. Marín; Jorge I. Tobón (Advances in Civil Engineering)
The influence of two lightweight aggregates (LWA) on concrete and the effects of cement substitution for nanosilica (NS) on the interfacial transition zone (ITZ) and cementitious matrix of concrete in resistance to attacks by magnesium sulfate (MgSO4) are researched in this work. The aggregates evaluated were perlite, which is a lightweight aggregate of open porous structure, and expanded clay (aliven) with closed porous structure. The variables included in the study were replacement percentage of coarse aggregates by lightweight coarse aggregates (0 and 100% by volume) and replacement percentage of cement by nanosilica (0 and 10% by weight). In the dosage of the mixtures, water/cementitious-material ratio constant of 0.35 was used. The LWA were characterized by XRD, XRF, and SEM techniques. Compressive strength, water absorption, and volume change in magnesium sulfate solution (according to ASTM C1012 for a period of 15 weeks) of lightweight concretes were evaluated. It was found that the nanosilica had effect on refinement in the pore system; however, the main incidence on the compressive strength and durability of lightweight concrete (LWC) was defined by the characteristics of lightweight aggregate used in its preparation.